Innovative Music Composition, “Reboisasi” | Komposisi Musik Inovatif, “Reboisasi” - iketut yogi anggayanto; Tri Haryanto (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Reboisasi is a musical works that is inspired by the surrounding environment that was once beautiful until the occurrence of illegal felling of trees and the desire to try to replant using the medium of expressing Gender Wayang as the main instrument as well as the addition of four flute instruments and one Tungguh Gong Pulu as supporting instruments. Reboisasi is an innovative musical composition which tends to explore new ideas or ideas even though it is still guided by existing traditional elements. In using panggul as a bat, Reboisasi's musical work uses one panggul which has two functions simultaneously, namely the stylist modifies the gendered panggul in the developmental part of the panggul by adding rubber on the surface that forms a semi-circle, by combining two different styles between Sukawati and Kayumas which aims to find different nuances of sound as well as in the technique of playing the technique of the kumbang atarung which in its processing plays fast, hard and suddenly soft techniques by rotating the panggul using the panggul on the rubber part.